PENGARUH SOLVABILITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI IDX LQ45 PADA BURSA EFEK INDONESIA PERIODE TAHUN 2015-2019 - Pradhipta Ayuningtyas; Batara Daniel Bagana (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The purpose of this study was to examine the effect of Solvency, Profitability and Activity variables on stock prices in banking companies listed on IDX LQ45 on the Indonesia Stock Exchange (IDX) in 2015-2019. Sample selection using purposive sampling method and obtained 5 samples of banking companies that meet the criteria. Data analysis used multiple linear regression. The results showed that the Debt to Equity Ratio variable had no effect on the Stock Price, the Return On Assets variable had no effect on the Stock Price, and the Price Earning Ratio variable had an effect on the Stock Price. Simultaneously DER, ROA and PER affect the stock price.